(untitled) (World Bulletin of Social Sciences, 2024)
In native language classes, the development of students’ connected speech is carried out in the context of text structure study and text composition exercises. Exercises that require writing are performed with creative activity, and on the basis of these exercises, students gain the experience of coherent, understandable, clear, effective expression of their thoughts, the creation of suitable sentences, connecting them, and elementary creativity. Scientists say, "A person who has experience of creative independent activity is always in a favorable position compared to people who use standard, rigid methods. He does his work better and faster" [1]. As it is often repeated in the methodological literature, a creative thinker, a person inclined to discovery, thinks about the development of both himself and the country where he lives. The creative process takes place in the form of mental, aesthetic, communicative activity, such as thinking, expressing the scenes that appear in one’s imagination with remembered words in different ways, and reflecting one’s feelings and one’s point of view in this process. The article talks about these issues